A woman in the culture, the culture of a woman: Caroline von Humboldt - Kowalska, Elžbieta M. M. (Literatūra, 2016)
The subject of this presentation is Wilhelm von Humboldt’s wife, Alexander von Humboldt’s sisterin-law, a close female friend of Lotte Schiller and of her sister, Caroline von Wolzogen, held in high regard by Goethe, admired by Schiller, the former Fräulein von Dacheröden from Erfurt, the future Caroline von Humboldt. She was the ancestress of one of the most respected and best German noble families, a mother of eight children, an intellectually gifted woman, in which the German ideals of femininity were fulfilled, who knew to lead the salons and to talk about arts and literature.